GPU-Based Optimization of a Free-Viewpoint Video System - Orman, Neal; Kim, Hansung; Sakamoto, Ryuuki; Toriyama, Tomoji; Kogure, Kiyoshi; Lindeman, Robert (Electronic letters on computer vision and image analysis, 2008)
We present a method for optimizing the reconstruction and rendering of 3D objects from multiple images by utilizing the latest features of consumer-level graphics hardware based on shader model 4.0. We accelerate visual hull reconstruction by rewriting a shape-from-silhouette algorithm to execute on the GPU's parallel architecture. Rendering is optimized through the application of geometry shaders to generate billboarding micr facets textured with captured images. We also present a method for handling occlusion in the camera selection process that is optimized for execution on the GPU. Execution time is further improved by rendering intermediate results directly to texture to minimize the number of data transfers between graphics and main memory. We show our GPU based system to be significantly more efficient than a purely CPUbased approach, due to the parallel nature of the GPU, while maintaining graphical quality.